Prediction of Fatigue-Creep Interaction Life of Aluminum Alloy AA7349 Using Electromechanical Devices - Hussain J. Al-Alkawi; Fikrat Abdul Kareem; Asmaa Abdulqasim Mohammed Ali (Engineering and Technology Journal, 2015)
In this present work, the behavior of AA7349 aluminum alloy under constant and cumulative creep-fatigue interaction has been studied by using an electrical system designed and built in order to investigate creep-fatigue interaction at different stress levels and temperatures. An hour-glass shaped specimen of AA7349 aluminum alloy has been subjected to a constant and variable creep-fatigue tests performed under rotating bending loads and stress control at stress ratio R=-1.The results of the creep –fatigue life have been studied byMiner rule and compared with the proposed and experimental methods. It was shown that theMinerrule and proposed modelgive reasonable results and they are in a good agreement with the experimental fatigue lifetimes.